Public Communication in Freefall
XXI, 254 p. 15 illus.
Keywords: This book addresses key challenges facing global political communication at a time in which transformations in political practice, media ecology and cultural expectations both threaten traditional democratic norms and point to potential new ways of enacting political democracy. Drawing upon the outstanding theoretical insights of Jay Blumler to our understanding of the norms and practices of political communication, but also critically interrogating and updating them where appropriate, the volume asks timely questions about what publicness and democracy mean in the 2020s. Many people are talking and writing about the crisis of political democracy, fewer are talking about the role of the media in relation to that crisis. While many scholars have responded in an ad hoc way to the various crises of populism, polarisation, mis and disinformation, this book shows how Jay Blumler’s scholarship provides us with the tools and framework to research and understand the changing communication environment systemically and rigorously. The book demonstrates the applicability and relevance of Blumler’s work in explicating the current crisis of communication and the need for fresh and radical thinking in tackling it. The book's breadth and depth of chapters from a broad range of scholars from the East and West, ranging from long-standing contributors to the field to those in the early stages of their career, combine to produce a thoughtful and provocative invitation to reflect upon the concept of a ‘crisis of public communication’. We expect this book to become a major source for political communication students and scholars. Stephen Coleman is Professor of Political Communication at the University of Leeds, UK. Frank Esser is Professor of International & Comparative Media Research in the Department of Communication and Media Research at the University of Zurich, Switzerland. Julie Firmstone is Professor of Journalism and Political Communication at the School of Media and Communication, University of Leeds, UK. Katy Parry is Professor of Media and Politics at the University of Leeds, UK. Chris Paterson is Professor of Global Communication at the School of Media and Communication, University of Leeds, UK.